2009
DOI: 10.1016/j.ejcts.2009.05.043
|View full text |Cite
|
Sign up to set email alerts
|

European results with a continuous-flow ventricular assist device for advanced heart-failure patients☆

Abstract: These results support the use of the HM II continuous-flow LVAD for long-term support as a bridge to transplantation and possibly for destination therapy. Future emphasis should focus on minimising adverse events such as infections, bleeding and neurological events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 6 publications
3
78
0
3
Order By: Relevance
“…MCS in adults is used as a bridge to transplantation, bridge to candidacy, or as destination therapy (Class IIa recommendation). 1 These devices lead to improved functional status and quality of life in this patient population 22,23 and have shown improved outcomes compared with optimal medical therapy. 24 However, MCS is not without complications.…”
Section: Discussionmentioning
confidence: 99%
“…MCS in adults is used as a bridge to transplantation, bridge to candidacy, or as destination therapy (Class IIa recommendation). 1 These devices lead to improved functional status and quality of life in this patient population 22,23 and have shown improved outcomes compared with optimal medical therapy. 24 However, MCS is not without complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical introduction of second-and third-generation nonpulsatile devices suggests that these devices can be used as a long-term approach. 2 Despite this, bleeding complications and thromboembolic events still remain the most serious adverse events of this therapy. Early experience with continuous flow device-related thrombosis and thromboembolic events led to a maximum tolerable regimen of antiplatelet and anticoagulation therapies.…”
mentioning
confidence: 99%
“…8 In our study group, LVAD was used in In a European study, outcomes after continuous flow LVAD implant showed a 1-year survival rate of 72%. 9 In the study of Teuteberg and associates, 8 the 2-year survival rate of patients supported for bridge to transplant was 78%, with rates of 70% for those with bridge to candidacy and 61% for those having the device for destination therapy. In our patient series, 8 patients (33.3%) died.…”
Section: Discussionmentioning
confidence: 99%